Writing and reality in three stories by Leonardo Padura: metonymic structure of prose as a process of dehierarchization - Mondoñedo, Marcos (2018)
This work develops an analysis of the rhetorical procedures of the prose of some stories by Leonardo Padura: "Según pasan los años", "El cazador", "La puerta de Alcalá". In them in a vaguely way a "flattening" of the several elements of narrative representation would be configured. This procedure can be described as a metonymic continuity or as a "textualization" of various planes of semiotic immanence, which would result in a special narrative verisimilitude: the fictional and historical reality keeps dissolving their limits with any apparent change in a pertinent level. In this way, the domains of fiction are extended to the field of life forms and these forms are projected to textual significance.